2014
DOI: 10.3748/wjg.v20.i39.14185
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and aging: Epidemiology to management

Abstract: Nonalcoholic fatty liver disease (NAFLD) is common in the elderly, in whom it carries a more substantial burden of hepatic (nonalcoholic steatohepatitis, cirrhosis and hepatocellular carcinoma) and extra-hepatic manifestations and complications (cardiovascular disease, extrahepatic neoplasms) than in younger age groups. Therefore, proper identification and management of this condition is a major task for clinical geriatricians and geriatric hepatologists. In this paper, the epidemiology and pathophysiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
203
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(228 citation statements)
references
References 237 publications
9
203
1
5
Order By: Relevance
“…NAFLD has been proven to be associated with sarcopenia [21][22][23] and low BMD [24]. The mechanisms incriminated seem to be mitochondrial dysfunction with loss of muscle mass for the occurrence of sarcopenia [21][22][23] and insulin resistance and/ or the accumulation of pro-inflammatory, pro-coagulant and pro-fibrogenic mediators for low BMD [24]. Corroborating our results with these data, we suggest that not only CHC but also antiviral treatment (peginterferon alpha 2a and ribavirin) may provoke sarcopenia and bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD has been proven to be associated with sarcopenia [21][22][23] and low BMD [24]. The mechanisms incriminated seem to be mitochondrial dysfunction with loss of muscle mass for the occurrence of sarcopenia [21][22][23] and insulin resistance and/ or the accumulation of pro-inflammatory, pro-coagulant and pro-fibrogenic mediators for low BMD [24]. Corroborating our results with these data, we suggest that not only CHC but also antiviral treatment (peginterferon alpha 2a and ribavirin) may provoke sarcopenia and bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NAFLD and insulin resistance may be associated with sarcopenia and the mechanism has been reported to be mitochondrial dysfunction with loss of muscle mass [21][22][23]. NAFLD has also been reported to be associated with a low BMD [24].…”
Section: Introductionmentioning
confidence: 99%
“…41 Finally, a recent study reports, men have a higher risk of more severe liver fibrosis compared to premenopausal women; however, post-menopausal women have a severity of liver fibrosis similar to men suggesting that estrogens may protect from fibrosis. 42 Advancing age increases the risk of NAFLD hepatic and extra-hepatic complications, 43 it is, therefore, expected that older NAFLD patients will have a higher likelihood of overall and disease-specific mortality. [44][45][46][47] Whether sex affects NAFLD natural history and mortality is uncertain, although studies have suggested a worse outcome in men.…”
Section: 15mentioning
confidence: 99%
“…Genetic or environmental factors (such as HCIAS) could lead to an earlier appearance of NAFLD. The appearance of NAFLD seems then more related to environmental factors than to intrinsic ageing, but the capacity to cope with the disease decreases with age (113) . Indeed, as previously described, fructose is able to disturb fatty acid metabolism, promoting NAFLD development, even in young individuals (114) .…”
Section: Secondary Diseasesmentioning
confidence: 99%
“…Removal of liver lipids can be provided by β-oxidation, fatty acid re-esterification, or export as VLDL-TAG. Epidemiological studies show that in men, the prevalence of NAFLD increases from young to middle age, and declines after the age of 50 or 60 years, whereas women are protected by oestrogens, and the prevalence increases after menopause but declines after the age of 70 years (113) . Genetic or environmental factors (such as HCIAS) could lead to an earlier appearance of NAFLD.…”
Section: Secondary Diseasesmentioning
confidence: 99%